Determination of the Standard Heterogeneous Rate Constant Through Scientific Research in Teaching - Secken, Nilgun (Asian Journal of Chemistry, 2010)
In this study, the cyclic voltammetry data obtained in laboratory environment through the determination of standard rate constant (ks) of the electron transfer with the help of cyclic voltammetry. At graduate level, when it comes to rate and rate constant, students mainly think of chemical reaction rates. However, emphasizing that there are rates that belong to the electron transfer at electrochemical reactions would enable students to look at electrochemical events through a different perspective. The importance of this study stems from its effect on students' comprehension that in electrochemical events, electrons have certain rates. The present study concerns with the determination of standard rate constant ks in an ethanolwater (1:5 v/v) mixture. In the light of the information attained from the literature, the ks calculation was done and the rate constant of the electron transfer was calculated together with the students.